The influence of Mind Set and motivation to entrepreneurial career Choice students University Putra Indonesia "YPTK" Padang: Pengaruh Mindset dan Motivasi Wirausaha pada Pilihan Karir Mahasiswa Universitas Putra Indonesia “YPTK” Padang - Dewi, Muharika; Endah Rahayu, Purwanti; Puspita Sari, Vivi; Rahmawati, Elmi; Putri Dika, Riri (International Journal of Technology Vocational Education and Training, 2020)
Not in accordance with career choices with education held by many factors, this study aims to carry out the testing set and entrepreneurial motivation regarding student career choices. The study was conducted by quantitative analysis, the sample was 46 students of the Teaching Faculty of Education, Universitas Putra Indonesia "YPTK" Padang, the instrument used a questionnaire, analysis of data related to the product moment formula, and performed multiple linear regression analysis and assisted with percentage research. The results showed students have a mindset of 74.4% (moderate), motivation 70.6% (moderate), only 10% who want to be entrepreneurs. Mindset Correlation with career choices 0.515, agreed 26%, motivation contributions with career choices 0.312 contriution 13%. Multiple regression 0.516 contributed 27%. The results of the research need to be conducted to study the character of entrepreneurship to strengthen the mindset and motivation in entrepreneurial career choices.